Electronic engineering and information science : selected, peer reviewed papers from the 2014 International Conference on Electronic Engineering and Information Science (ICEEIS 2014), June 21-22, 2014, Harbin, China - Yin, Jinghua; Su, Bo; Wang, Dongxing (Advanced materials research, 2014)
Collection of selected, peer reviewed papers from the 2014 International Conference of Electronic Engineering and Information Science (ICEEIS 2014), June 21-22, 2014, Harbin, China. The 209 papers are grouped as follows: Chapter 1: Electronic Engineering, Chapter 2: Information Science and Information Technologies, Chapter 3: Computational Mathematics and Data Mining, Chapter 4: Image Processing and Computer Vision, Chapter 5: Communication and Signal Processing, Chapter 6: Mechatronics, Control and Automation, Chapter 7: Methods, Devices and Systems for Measurement and Monitoring, Chapter 8: Power Engineering and Power Supply, Chapter 9: Engineering of Weapons Systems, Chapter 10: Mechanical Engineering, Chapter 11: Material Science and Technologies of Processing, Chapter 12: Engineering Management and Logistics Keyword: Electronic Engineering, Image Processing, Communication and Signal Processing, Power Engineering, Material Science, Mechatronics Yin, Su, and Wang presents students, academics, researchers, and practicing electronics engineers and information scientists with a collection of selected peer-reviewed papers from the material presented at the 2014 International Conference on Electronic Engineering and Information Science, held Harbin, China. The materials collected in the volume are organized in twelve chapters, covering electronic engineering, information science and information technologies, computational mathematics and data mining, image processing and computer vision, communication and signal processing, and a great many other related subjects. -- Electronics-- Information science-- Materials science.